KLASIFIKASI JENIS IKAN FAMILIA CYPRINIDAE DI SUNGAI PANGI DESA PENGGUMBUK KECAMATAN RANTAU BAYUR KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Dian Mutiara (Universitas PGRI Palembang, 2014)
Research of clasification of fish cyprinidae Family at Pangi river Pengumbuk village, Banyuasin regency Sumatera Selatan province on Agustus-September 2013. This research utilited the direct observation method by collecting fish samples which were caught by fisherman along Pengumbuk river. The result of the research geted 8 genera and 9 species.Key words : pengumbuk river, Classification, Cyprinidae, spesies.